Digital Preservation of South Korean Cultural Heritage: Focusing on UNESCO World Heritage Sites - Khamitova, Nazerke; Belyalova, Aigerim; Kim, Sangheon (Research Journal in Advanced Humanities, 2026)
This study explores the opportunities and challenges associated with the digitization of UNESCO World Heritage Sites in South Korea. The country has emerged as a global leader in leveraging digital technologies to enhance the accessibility of rich cultural assets. The study finds important advantages such as improved public participation, global reach, and the digital transformation of Korean culture. At the same time, the study highlights significant challenges such as technical limitations, budgetary constraints, cultural sensitivity, and data management problems. Through qualitative interviews with key stakeholders, the research provides a comprehensive perspective of the present landscape of digitalization activities. The findings under-score the importance of collaboration among government agencies, private sector entities, and local communities to address existing barriers and fully realize the potential of digital initiatives. Finally, this study intends to provide strategic recommendations aimed at ensuring the effective digitization, protection, and long-term accessibility of South Korea’s cultural heritage.